2012
DOI: 10.1039/c2cc17183j
|View full text |Cite
|
Sign up to set email alerts
|

NHC-catalyzed thioesterification of aldehydes by external redox activation

Abstract: The NHC-catalyzed thioesterification of aromatic or aliphatic aldehydes with a range of thiols was developed in the presence of a stoichiometric amount of an organic oxidant. Among the oxidants examined, phenazine was shown to give the best results in terms of chemical yield and compatibility with thiols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Along with TBD, other bases such as DBU (1,8-diazabicycloundec-7ene), MTBD (7-methyl-1,5,7- 4.4.0]dec-5ene, pK a > 24 in CH 3 CN), [24] Cs 2 CO 3 , Rb 2 CO 3 , t-BuOK, KHMDS showed activity in the esterification (entries [13][14][15][16][17][18]. Along with TBD, other bases such as DBU (1,8-diazabicycloundec-7ene), MTBD (7-methyl-1,5,7- 4.4.0]dec-5ene, pK a > 24 in CH 3 CN), [24] Cs 2 CO 3 , Rb 2 CO 3 , t-BuOK, KHMDS showed activity in the esterification (entries [13][14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with TBD, other bases such as DBU (1,8-diazabicycloundec-7ene), MTBD (7-methyl-1,5,7- 4.4.0]dec-5ene, pK a > 24 in CH 3 CN), [24] Cs 2 CO 3 , Rb 2 CO 3 , t-BuOK, KHMDS showed activity in the esterification (entries [13][14][15][16][17][18]. Along with TBD, other bases such as DBU (1,8-diazabicycloundec-7ene), MTBD (7-methyl-1,5,7- 4.4.0]dec-5ene, pK a > 24 in CH 3 CN), [24] Cs 2 CO 3 , Rb 2 CO 3 , t-BuOK, KHMDS showed activity in the esterification (entries [13][14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…[8] Formation of acylazolium ions can be achieved by employing substrates able to undergo internal redox processes. [6,9] It was also found that MnO 2 , [10] azobenzene, [11] riboflavin, [12] phenazine, [13] TEMPO [14] and quinones [15] are effective external oxidants for oxidation of the Breslow intermediate to give the corresponding reactive acylazolium ion intermediate. [5] However, the internal redox active substrates need to be specially designed and the necessity to add an organic or inorganic stoichiometric external oxidant in the latter processes lead to an increase of costs and chemical waste which will hamper application of these strategies on a larger scale.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an N ‐heterocyclic carbine (NHC)‐catalyzed coupling reaction of thiols with aldehydes to produce thioesters was developed by Takemoto and coworkers. This method has some drawbacks such as the use of expensive carbenes and the requirement of stoichiometric amount of phenazine as oxidant in the reaction . The C–S bond formation between pentafluorophenyl disulfide and aldehydes was successfully accomplished by Kita et al .…”
Section: Introductionmentioning
confidence: 99%
“…This method has some drawbacks such as the use of expensive carbenes and the requirement of stoichiometric amount of phenazine as oxidant in the reaction. 7 The C-S bond formation between pentafluorophenyl disulfide and aldehydes was successfully accomplished by Kita et al; however, diaryl and dialkyl disulfides are not suitable as coupling partners in this system. 8 Bandgar and coworkers reported the synthesis of thioesters from aryl thiols and aldehydes in the presence of Dess-Martin periodinane and NaN 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[14] The reaction provides trans -lactam 3a [15] in trace amount (Table 1, entry 1). To shed light on the issue, NMR experiments were performed using 2a , the catalyst C1 and DBU, which revealed an interaction between carbene and 2a causing catalyst inactivation.…”
mentioning
confidence: 99%